The effectiveness of conservation farming as a strategy for ensuring food security in Zimbabwe: a case of Gwanda south district, ward 19. - Dube, Amie (Midlands State University, 2017)
The purpose of the study was to examine how the practice of conservation farming is impacting on household food security in Gwanda District. In particular, it examines four pillars of food security which are: food availability, accessibility, utilization and stability. Particular attention was given to also examine the extent of conservation farming on food security. A sample of 20 farmers under conservation farming was selected to as respondents. The major objective of the study was to examine whether the practice of conservation farming is effective in ensuring food security. Questionnaires, interviews and focus group discussions were used to gather data from the sampled households. Data was collected through qualitative and quantitative method. The findings from the research indicate that many farmers in Zimbabwe have adopted conservation farming. This has however ensured food availability, utilization, accessibility and stability within the households. This has been noticed through number of meals per day, assets ownership and types of crops being grown. Nevertheless, some of the challenges faced by farmers in their quest to practicing conservation farming include shortage of inputs, old age, shortage of labour and climate change. Regardless of these challenges, farmers have been persisting in practicing conservation farming.